2014
DOI: 10.3390/molecules19044847
|View full text |Cite
|
Sign up to set email alerts
|

Structural Modeling of Djenkolic Acid with Sulfur Replaced by Selenium and Tellurium

Abstract: Abstract:The comparative structural modeling of djenkolic acid and its derivatives containing selenium and tellurium in chalcogen sites (Ch = Se, Te) has provided detailed information about the bond lengths and bond angles, filling the gap in what we know about the structural characteristics of these aminoacids. The investigation using the molecular mechanics technique with good approximation confirmed the available information on X-ray refinements for the related compounds methionine and selenomethionine, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Fzf1p is composed of five zinc fingers (ZFs) and plays a positive role in the transcription of ssu1 ( 26 ). Given the tight regulatory relationship between ssu1 and fzf1 and that they were both mutated in most evolved groups within several positions coincidentally, these results suggested that ssu1 and fzf1 are likely to perform homogeneous functions in selenium metabolism combined with the chemical similarity between selenium and sulfur ( 27 29 ). Therefore, we investigated the latent functions of ssu1 and fzf1 in the selenium tolerance of yeasts and then confirmed that both ssu1 and fzf1 indeed play vital roles, while the other four most frequently mutated genes ( fcy21 , cos9 , mnn4 , and bio3 ) screened by sequencing analysis were found to be irrelevant for selenium tolerance (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…Fzf1p is composed of five zinc fingers (ZFs) and plays a positive role in the transcription of ssu1 ( 26 ). Given the tight regulatory relationship between ssu1 and fzf1 and that they were both mutated in most evolved groups within several positions coincidentally, these results suggested that ssu1 and fzf1 are likely to perform homogeneous functions in selenium metabolism combined with the chemical similarity between selenium and sulfur ( 27 29 ). Therefore, we investigated the latent functions of ssu1 and fzf1 in the selenium tolerance of yeasts and then confirmed that both ssu1 and fzf1 indeed play vital roles, while the other four most frequently mutated genes ( fcy21 , cos9 , mnn4 , and bio3 ) screened by sequencing analysis were found to be irrelevant for selenium tolerance (Fig.…”
Section: Resultsmentioning
confidence: 93%